Public perception of ex-mental patients. - Fracchia, J (1976)
Data are presented from two studies which show that perceptions of ex-mental patients appear to derive from a lack of information and that the provision of information alters the perception of former patients. Perceived unpredictability of behavior and dangerousness seem to form a dyad that causes the public to fear the mentally ill. More positive perceptions of mildly ill ex-mental patients were obtained when subjects were given short paragraphs describing typical behaviors and symptoms. These findings support the notion that a fear-motivated threat recoil cycle process is likely to be evoked by attempts to establish locally based treatment facilities, particularly in residential communities.